Comparative Molecular Analyses of Esophageal Squamous Cell Carcinoma, Esophageal Adenocarcinoma, and Gastric Adenocarcinoma. (4th June 2018) - Salem, Mohamed E.; Puccini, Alberto; Xiu, Joanne; Raghavan, Derek; Lenz, Heinz‐Josef; Korn, W. Michael; Shields, Anthony F.; Philip, Philip A.; Marshall, John L.; Goldberg, Richard M.
Abstract: Background: Gastroesophageal cancers are often grouped together even though cancers that originate in the esophagus often exhibit different histological features, geographical distribution, risk factors, and clinical characteristics than those originating in the stomach. Herein, we aimed to compare the molecular characteristics of three different gastroesophageal cancer types: esophageal squamous cell carcinoma (ESCC), esophageal adenocarcinoma (EAC), and gastric adenocarcinoma (GAC). Subjects, Materials, and Methods: In total, 3, 342 gastroesophageal cancers were examined. Next‐generation sequencing was performed on genomic DNA isolated from formalin‐fixed paraffin‐embedded tumor samples using the NextSeq platform. Tumor mutational burden was measured by counting all nonsynonymous missense mutations, and microsatellite instability was examined at over 7, 000 target microsatellite loci. Immunohistochemistry and in situ hybridization techniques were also performed. Results: When compared with EAC and GAC, ESCC showed significantly lower mutational rates within APC, ARID1A, CDH1, KRAS, PTEN, and SMAD4, whereas more frequent mutations were observed in BAP1, CDKN2A, FOXO3, KMT2D, MSH6, NOTCH1, RB1, and SETD2 . Human epidermal growth receptor 2 (HER2) overexpression was observed in 13% of EAC compared with 6% of GAC and 1% of ESCC ( p  < .0001). Compared with EAC and GAC, ESCC exhibited higher expression of programmed death‐ligand 1 (PD‐L1) (27.7% vs. 7.5% vs. 7.7%, p  < .0001). We observed that FGF3, FGF4, FGF19, CCND1 (co‐localized on 11q13), and FGFR1 were significantly more amplified in ESCC compared with EAC and GAC ( p  < .0001). Conclusion: Molecular comparisons between ESCC, EAC, and GAC revealed distinct differences between squamous cell carcinomas and adenocarcinomas in each platform tested. Different prevalence of HER2/neu overexpression and amplification, and immune‐related biomarkers between ESCC, EAC, and GAC, suggests different sensitivity to HER2‐targeted therapy and immune checkpoint inhibition. These findings bring into question the validity of grouping patients with EAC and ESCC together in clinical trials and provide insight into molecular features that may represent novel therapeutic targets. Implications for Practice: This study highlights the genomic heterogeneity of gastroesophageal cancers, showing striking molecular differences between tumors originating from different locations. Moreover, this study showed that esophageal squamous cell carcinomas exhibit a unique molecular profile, whereas gastric adenocarcinomas and esophageal adenocarcinomas have some similarities, supporting the fact that adenocarcinomas and squamous cell carcinomas are completely different diseases, irrespective of the tumor location. This raises the question of whether treatment of gastroesophageal tumors should be determined according to histological subtype and molecular targets rather than anatomical site. These findings provide insights that could enable physicians to better select patients and inform therapeutic choices in order to improve clinical outcome. Abstract : To improve the precision of targeted and conventional therapy, the molecular profiles of gastroesophageal tumors were assessed, with the aim of comparing the molecular characteristics of esophageal adenocarcinoma, esophageal squamous cell carcinoma, and gastric adenocarcinoma. Results are reported in this article.